Structural-dependent effects of dietary fibers in colon cancer: Focus on dietary fiber naturally changed by the papaya ripening - Prado, Samira Bernardino Ramos do (2019)
Dietary fiber (DF) consumption is related with several healthy benefits such as the decreasing risk of colon cancer development. The DF is not digested by the digestive enzymes and reach to colon where is fermented by the colonic microbiota. The fermentation process releases metabolites as short chain fatty acids (SCFA) such as butyrate, propionate and acetate. Besides the fermentation process, the DF can directly interact with intestinal epithelial cells inducing mechanism that can also be related with the associated DF consumption benefits. The lack of information regarding DF and colon cancer are due to the complexity of both the cancer and the DF structure. The papayas DF are derived from the fruit cell wall, and they are probably naturally modified during ripening through a massive polysaccharide hydrolysis, because papayas show a very fast pulp softening. Due to the lack of information about DF and their beneficial effects to human health as well as the possibility of the natural papaya ripening to modifying the DF presented in the fruit pulp, the present thesis had as the primary objectives: 1) to evaluate how the cell-wall degrading enzymes affect the fruit cell wall solubilization and molecular weight; 2) to investigate the direct effects of the papaya pectin derived from unripe to ripe papayas in cancer cell lines, in galectin-3 interaction and in HEK cells expressing pattern recognition receptors (PRR); 3) to evaluate the human colonic in vitro fermentation using DF from unripe and ripe papayas as substrates; 4) to conduct an in vivo experiment using rats with pre-neoplastic colon lesions while receiving a diet with DF from unripe and ripe papayas. The endopolygalacturonases were the main enzymes acting on the solubilizing papaya cell wall pectin affecting both the papaya firmness and pectin structure. Overall, the papayas DF showed a ripening dependent structureeffects. In the cancer cell lines experiments, the ripe papayas pectin showed a more pronounced effects in inducing cancer cell death, inhibiting cancer cells migration and aggregation, activating PRR as toll-like receptors and inhibiting the pro-metastatic protein galectin-3. The DF from papayas also showed different aspects in colonic in vitro fermentation regarding the DF utilization by the bacteria and the bacteria abundance profile. Lastly, the animals receiving the diet with the DF from ripe papayas had less aberrant crypt foci in colon than the animals that received the DF from unripe papayas or cellulose (AIN-93G DF). Therefore, the study of papaya DF was carried out both during papaya ripening and its biological effects in vitro and in vivo, generating unprecedented results relating the endogenous biochemical changes of the fruits during maturation with the possible beneficial effects of their ingestion for health human.